Cause and control of hydrolytic rancidity in raw milk - I.J. Jeon (Kansas Agricultural Experiment Station Research Reports, 1988)
One of the common and important off-flavors in milk is hydrolytic rancidity or lipolyzed flavor. The rancidity results from hydrolytic cleavage of fatty acids from milk fat by the enzyme lipase and their release as free acids. The release of these acids in milk, even in very small amounts, imparts a bitter taste and a sharp, unpleasant aroma. The off-flavor is often described as "goaty", "butyric", "soapy", and "bitter" The term "bitter", however, is ambiguous because bitter flavors can occur from the result of protein breakdowns. Nevertheless, both farm and dairy plant problems may lead to its development. Once an objectionable level is reached, no processing technique will eliminate it.; Dairy Day, 1988, Kansas State University, Manhattan, KS, 1988;
Keywords: Kansas Agricultural Experiment Station contribution; no. 89-107-S; Dairy; Hydrolytic rancidity; Raw milk; Lipase